2020
DOI: 10.24912/je.v25i1.632
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pembiayaan Mudharabah dan Musyarakah Terhadap Return On Asset BPRS di Indonesia

Abstract: As an intermediary institution, BPRS has facilities in the field of financing where Islamic banks channel funds obtained from the public in the form of deposits. This research was conducted to determine the effect of mudharabah and musyarakah financing simultaneously and partially on the Return On Assets of Islamic People's Financing Banks in Indonesia. The object of research is all Islamic People's Financing Banks in Indonesia from January 2016 to December 2018. The research approach used is a quantitative ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
0
0
1
Order By: Relevance
“…Research conducted by Fatimah & Diana (2021), Mirandha (2021), Sanulika &Hidayati (2020) andChasanah et., al. (2020) found that mudharabah has a significant positive effect either partially or simultaneously on profitability, while the research conducted by Islamiyati & Diana (2022) and Hakim & Hasanah (2020) revealed that mudharabah does not have a significant effect on profitability, either partially or simultaneously.…”
Section: Figure 1 Islamic Financial Assetsmentioning
confidence: 99%
“…Research conducted by Fatimah & Diana (2021), Mirandha (2021), Sanulika &Hidayati (2020) andChasanah et., al. (2020) found that mudharabah has a significant positive effect either partially or simultaneously on profitability, while the research conducted by Islamiyati & Diana (2022) and Hakim & Hasanah (2020) revealed that mudharabah does not have a significant effect on profitability, either partially or simultaneously.…”
Section: Figure 1 Islamic Financial Assetsmentioning
confidence: 99%
“…Penelitian oleh (Hakim & Hasanah, 2020) tentang Pengaruh Pembiayaan Mudharabah dan Musyarakah Terhadap Return on Asset BPRS di Indonesia menemukan bahwa pembiayaan mudharabah dan musyarakah secara simultan tidak berpengaruh signifikan terhadap Return on Asset Bank Pembiayaan Rakyat Syariah di Indonesia. Secara parsial, pembiayaan mudharabah tidak berpengaruh signifikan positif, sementara pembiayaan musyarakah tidak berpengaruh signifikan negatif terhadap Return on Asset Bank Pembiayaan Rakyat Syariah di Indonesia.…”
Section: Pendahuluanunclassified
“…It can be said that profit sharing is one of the operational practices that Islamic banks are definitely doing. According to Prasetyo, (2011), Kristina &; Nurdiansyah, (2023), Saputra &; Atmanti, (2022), Mauizhotul Hasanah, (2020) shows that profit sharing financing has a positive and significant influence on Falah Laba, so the greater the profit sharing financing, the Profit Falahwill is increasing. Based on the study of theory and the results of previous research, hypotheses can be formulated as follows:…”
Section: The Effect Of Profit Sharing On Profit Falahmentioning
confidence: 99%